PROVIDING EDUCATION TO STUDENTS AT THE DARUL ILMI BATANG Islamic Boarding School THE IMPORTANCE OF SPORT WARMING FOR THE ELDERLY - ahmad khafis khafis (STKIP Muhammadiyah Kuningan Secretariat Jurnal Muhammadiyah Untuk Olahraga Indonesia. Building A106 Street of Murtasiah Soepomo No 28b, 45511 Kuningan - West Java Telephone : 0232-874085 Homepage : E-mail, 2023)
PROVIDING EDUCATION TO STUDENTS AT THE DARUL ILMI BATANG Islamic Boarding School THE IMPORTANCE OF SPORT WARMING FOR THE ELDERLY One of the community service activities is socialization Providing Education on the Importance of Sport for the Elderly. We created this Sports Movement for the Elderly because we see that many elderly people are experiencing biological decline as visible symptoms of physical decline, one of which is cognitive decline. Cognitive function is related to physical activity that affects its structure and function, every physical movement that is carried out provides stimulation to the brain. Declining physical abilities have resulted in the elderly being a high-risk group in handling health problems. We also socialize this to children, even though they are not yet old, at least they understand and understand that later when they are elderly they still need to exercise. We socialize this activity smoothly and fully excitement.The socialization on Education on the Importance of Sport for Seniors was carried out on Saturday, December 17, 2022 at 13.00 WIB at Pondok Darul Ilmi Batang after rest activities. In the student team, which numbered 4 people, each of them had their respective assignments, including as presenters about the sequence of Warming up, Core Movement, and Cooling down and some as photo documentaries. , it turns out that many children ask about sports at an advanced age, here we can conclude that there is very good and conducive communication from the presenters and students which can be understood by students, although there are some students who still do not understand about participating in sports practices for the elderly Keywords: Sport, Elderly